FROM CRAFT SCHOOL TO NATIONAL RESEARCH UNIVERSITY OF TECHNIQUE AND TECHNOLOGY - Anatoliy A. Aleksandrov (Moscow Polytechnic University, 2016)
The article highlights the features of engineering training at engineering training, the specific character of so call «Russian method» of engineers' training. The author formulates the main areas of university development as a national research university and focuses on historical and conceptual continuity in organization of education process. Nowadays the«Russian method» has transformed into a new model implying organization of research and education centers where students get the fundamentals of technical sciences and implement them in real projects and create real products.